Travel back to school: use of humour in intertwining of objective authenticity and staged experiences - Maja Turnsek; Tatjana Zupančič; Barbara Pavlakovič (The European Journal of Humour Research, 2019)
From living museums to heritage escape rooms, edutainment is becoming a norm in interpretation of heritage, yet not much is known, of the specific role humour plays in the creation and performance of such educational products. This paper explores concepts of authenticity, functions of humour and experience design dimensions on an in-depth case study of a tourism product. The product “Smart Head Primary School” is a re-enactment of teaching as it occurred in the 1950’s in Slovenia. It gained a high extent of popularity primarily due to its extensive inclusion of humour. The product uses the role of a strict teacher to interpret to the “pupils” (visitors) the prime elements of the regions’ heritage. To analyse the intertwining of humour with heritage interpretation, the authors combine two research methods: (a) the in-depth analysis of a transcribed video-recording of a sample performance including the self-analysis and the reflections by one of the “teachers” and (b) a survey distributed to the visitors of the product. The results show that with the use of humour, visitors are able to perceive and recognize the difference between objective and constructive authenticity more effectively.